Resilience and motivation: a training course for primary teachers - Sabrina Schiavone (Firenze University Press, 2016)
The research starts from a reflection on educational resilience as a prerequisite for the development of inclusive competences for teachers. 42 teachers and 226 students were involved from three primary schools in the province of Trapani and Palermo, situated in contexts at risk of cultural degradation, early school dropout and high multiculturalism. Research enabled teachers to know and deal with the sense of resilience, not yet widely known, in view of the educational/developmental context, providing them with tools and materials to be used in the classroom, in order to carry out activities, promote resilience and support processes of inclusion by providing causes for reflection on their professional motivation. Resilienza e motivazione: un percorso per la formazione dei docenti di scuola primaria La ricerca nasce dalla riflessione sull'aspetto educativo della resilienza come presupposto per lo sviluppo di competenze inclusive per i docenti. Sono stati coinvolti 42 docenti e 226 studenti di tre scuole primarie della provincia di Trapani e Palermo, situate in contesti a rischio di degrado culturale, dispersione scolastica ed alta multiculturalità. Il percorso di ricerca ha permesso agli insegnanti di conoscere e di affrontare il costrutto di resilienza, non ancora ampiamente conosciuto, in un'ottica di tipo educativo/evolutivo fornendo loro strumenti e materiali da applicare in classe per la realizzazione di attività per promuovere la resilienza e favorire processi di inclusione ed offrendo spunti di riflessione sulla loro motivazione alla professione.